Deciphering direct transcriptional effects of epigenetic compounds through large-scale new RNA profiling - Leonard Hartmanis; Daniel Ramsköld; Gert-Jan Hendriks; Per Johnsson; Gustav Hallén; Ran Ma; Anton J. M. Larsson; Salomé Hahne; Christoph Ziegenhain; Johan Hartman; Rickard Sandberg (Nature Communications)
Abstract Examining direct transcriptional effects of genetic and chemical perturbations is crucial for understanding gene expression mechanisms. Standard RNA-seq experiments often overlook these direct effects, and current methods for profiling nascent RNA are usually time-consuming. Here, we adapted single-cell 4sU-based sequencing into a scalable, automated mini-bulk format to profile new RNA in smaller cell populations. This approach enabled us to map the direct transcriptional effects of epigenetic regulators. Brief exposure to SAHA (an HDAC inhibitor) revealed hundreds of directly responsive genes, many showing altered transcriptional bursting kinetics, with promoter regions enriched in binding sites for factors including bromodomain proteins. Profiling 83 epigenetic compounds uncovered direct transcriptional impacts from inhibitors of bromodomain proteins, histone deacetylases, and histone demethylases. Notably, chemically similar HDAC inhibitors elicited concordant direct responses and intronic expression analyses mirrored the direct effects seen in new RNA. This work highlights powerful approaches for investigating transcriptional mechanisms.